2016
DOI: 10.1371/journal.pone.0165635
|View full text |Cite
|
Sign up to set email alerts
|

The Bacteriohopanepolyol Inventory of Novel Aerobic Methane Oxidising Bacteria Reveals New Biomarker Signatures of Aerobic Methanotrophy in Marine Systems

Abstract: Aerobic methane oxidation (AMO) is one of the primary biologic pathways regulating the amount of methane (CH4) released into the environment. AMO acts as a sink of CH4, converting it into carbon dioxide before it reaches the atmosphere. It is of interest for (paleo)climate and carbon cycling studies to identify lipid biomarkers that can be used to trace AMO events, especially at times when the role of methane in the carbon cycle was more pronounced than today. AMO bacteria are known to synthesise bacteriohopan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 128 publications
3
57
1
Order By: Relevance
“…The hopanoid C-3 methylase (hpnR) is phylogenetically diverse among bacteria (Welander and Summons, 2012). More recently, 3Me-aminotriol was identified in haloalkaliphilic (Type I) Methylomicrobium alcaliphilum (Banta et al, 2015;Rush et al, 2016) and was also detected in a Sphagnum peat (Talbot et al, 2016). In the latter, 3Me-aminotriol abundances mirrored the depth profile of aminopentol, providing circumstantial evidence that 3Me-aminotriol could be produced by other Type I methanotrophs.…”
Section: Aminopolyol Sourcesmentioning
confidence: 98%
See 2 more Smart Citations
“…The hopanoid C-3 methylase (hpnR) is phylogenetically diverse among bacteria (Welander and Summons, 2012). More recently, 3Me-aminotriol was identified in haloalkaliphilic (Type I) Methylomicrobium alcaliphilum (Banta et al, 2015;Rush et al, 2016) and was also detected in a Sphagnum peat (Talbot et al, 2016). In the latter, 3Me-aminotriol abundances mirrored the depth profile of aminopentol, providing circumstantial evidence that 3Me-aminotriol could be produced by other Type I methanotrophs.…”
Section: Aminopolyol Sourcesmentioning
confidence: 98%
“…Aminopentol and aminotetrol have been primarily detected in proteobacterial Type I and Type II methanotrophs, respectively (Rohmer et al, 1984;Talbot et al, 2001;van Winden et al, 2012) and their presence in near-shore marine sediments has been attributed to the supply of continental wetland-derived OC off, for example, the Amazon and Congo rivers (Talbot et al, 2014;Wagner et al, 2014). Although aminopentol has thus far been regarded as the most taxonomically specific BHP methanotrophy proxy, Rush et al (2016) recently challenged its proficiency as proxy for Type I aerobic methanotrophy except in the case of terrestrial wetland methanotrophy (Rush et al, 2016). We observe a general decrease of both aminopentol and aminotetrol abundances from station Miss R to station GOM 540 (Figure 8).…”
Section: Aminopolyol Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…While bacteriohopanetetrol (BHT) is produced by diverse bacteria and is ubiquitous in modern environments (e.g., freshwater, marine, and soil), other structural variations are associated with particular taxonomic or environmental sources. For example, amino‐BHPs are prevalent in methanotrophs (Blumenberg et al., ; Rush et al., ), a stereoisomer of BHT (BHT II) has been associated with anammox bacteria and suboxic–anoxic environments (Matys et al., ; Rush et al., ; Sáenz, Wakeham, Eglinton, & Summons, ), and hopaneribonolactone and anhydrobacteriohopanetetrol have been proposed as indicators of oxidizing and reducing environments, respectively (Bradley, Pearson, Sáenz, & Marx, ). Identifying and understanding taxonomic sources and environmental conditions that prompt the production of particular hopanoids in diverse modern environments continues to be a geobiologically significant research topic.…”
Section: Introductionmentioning
confidence: 99%
“…β-hydroxy FAs have been detected in a range of methanotrophic bacteria (Bowman et al, 1991) and their source has been identified as the lipid A component of lipopolysaccharides (Wollenweber and Rietschel, 1990), which are a major constituent of the outer membrane of Gram-negative bacteria (Keinänen et al, 2003; Wollenweber and Rietschel, 1990). Methanotrophs also produce bacteriohopanepolyols (BHPs) which can be tetra, penta or hexafunctionalised (Cvejic et al, 2000a; van Winden et al, 2012b; Rush et al, 2016; Osborne et al, 2017). BHPs have been identified with a range of modifications including 3β-methylation and unsaturations at the Δ 6 and Δ 11 positions (Talbot et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%